Kabul, 1841-42 - Yorke, Edmund (Stroud, Gloucestershire Spellmount, 2012)
Kabul is a name that has had much resonance in current affairs over the last few years, however its place in military history can be charted much further back to the first British incursions into Afghanistan during the 19th century.
Include Index
Keywords: Afghanistan -- Afghanistan--Kabul -- British Intervention (Afghanistan : 1838-1842)